Association Between MTHFR C677T Polymorphism and Susceptibility to Autism Spectrum Disorders: A Meta-Analysis in Chinese Han Population - Li, Chen-Xi; Liu, Yi-Guang; Che, Yue-Ping; Ou, Jian-Lin; Ruan, Wen-Cong; Yu, Yong-Lin; Li, Hai-Feng (Frontiers in Pediatrics, 2021)
Methylenetetrahydrofolate reductase (MTHFR) plays a critical role in regulating homocysteine concentration in the blood. Prior studies have focused on the influence of MTHFR C677T on autism susceptibility, but the conclusions are still mixed and no analysis on Chinese population has been employed. We carried out a meta-analysis to comprehensively evaluate the genetic association of MTHFR C677T polymorphism with autism susceptibility in Chinese population. A large-scale literature retrieval was carried out based on various databases including PubMed, Embase, Wan Fang and Chinese National Knowledge Infrastructure (CNKI) to 31st July, 2020. The strength of correlation was assessed by odds ratios (ORs) and 95% confidence intervals (95% CIs). Moreover, subgroup analysis was conducted to further ascertain such relationship in different regions. A total of 2258 cases and 2073 controls were included in the present meta-analysis study. MTHFR C677T showed a significant correlation with increased ASD susceptibility under all genetic models in overall analysis, and stratification analysis by region also revealed a similar association in Northern Han subgroup under the same contrast, but not in Northern Han subgroup. In Conclusion, MTHFR C677T polymorphism is associated with the increased risk of autism in China, especially in the north. The different associations may be related to people's different folate and vitamin B12 concentrations in the two regions. Given that those mothers and children who are generally susceptible to autism, prenatal folate and vitamin B12 may reduce the risk that children suffer from autism, especially in northern China. In this regard, more well-designed studies with large sample size are expected to elucidate the conclusions.